2017
DOI: 10.3122/jabfm.2017.06.170183
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians’ Perceived Prevalence, Safety, and Screening for Cigarettes, Marijuana, and Electronic-Nicotine Delivery Systems (ENDS) Use during Pregnancy

Abstract: Objective Assess perceptions of prevalence, safety, and screening practices for cigarettes and secondhand smoke exposure (SHSe), marijuana (and synthetic marijuana), electronic nicotine delivery systems (ENDS; e.g., e-cigarettes), nicotine replacement therapy (NRT), and smoking-cessation medications during pregnancy, among primary care physicians (PCPs) providing obstetrical care. Methods A web-based, cross-sectional survey was e-mailed to 3750 US physicians (belonging to organizations within the Council of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In the U.S., surveys of health professionals caring for pregnant women have indicated that many appear to have concerns about the use of e-cigarettes; obstetricians and gynecologists were uncertain about how to advise on e-cigarettes due to lack of guidance [35], and of US family physicians who provided obstetric care, most respondents thought that e-cigarettes are unsafe to use during pregnancy [36]. Many US quitline professionals also have negative beliefs about e-cigarettes outside of pregnancy [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., surveys of health professionals caring for pregnant women have indicated that many appear to have concerns about the use of e-cigarettes; obstetricians and gynecologists were uncertain about how to advise on e-cigarettes due to lack of guidance [35], and of US family physicians who provided obstetric care, most respondents thought that e-cigarettes are unsafe to use during pregnancy [36]. Many US quitline professionals also have negative beliefs about e-cigarettes outside of pregnancy [37].…”
Section: Discussionmentioning
confidence: 99%
“…Physicians and other obstetric providers undoubtedly play a key role in educating pregnant women on risks of drug use in pregnancy. Improvements in identifying women who use marijuana and other drugs would assist in achieving this goal …”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a study of 115 physicians at Saint Louis University Hospital, provider knowledge and practices regarding ECIGs were assessed, and results indicated that 51% of respondents viewed the products as a tool for harm reduction, while 53% reported patients inquiring about using ECIGs as a smoking cessation aid (Kanchustambham et al, 2017). Somewhat similarly, a survey of 417 family medicine physicians (providing labor and delivery care) in a Texas based study found almost half believed ECIGs users were at a lower risk for cancer compared to conventional cigarette smokers, and 4.4% of providers reported prescribing or recommending ECIGs to pregnant smokers who desired to quit (Northrup et al, 2017). Overall, perceptions of ECIGs among healthcare providers are mixed, and the existing research highlights the need for these professionals to receive accurate, up-to-date information about ECIGs so they can guide their patients appropriately.…”
Section: What Are Healthcare Provider's Perceptions About Ecigs?mentioning
confidence: 99%